2008
DOI: 10.2337/db08-0516
|View full text |Cite
|
Sign up to set email alerts
|

Common Missense Variant in the Glucokinase Regulatory Protein Gene Is Associated With Increased Plasma Triglyceride and C-Reactive Protein but Lower Fasting Glucose Concentrations

Abstract: OBJECTIVE-Using the genome-wide association approach, we recently identified the glucokinase regulatory protein gene (GCKR, rs780094) region as a novel quantitative trait locus for plasma triglyceride concentration in Europeans. Here, we sought to study the association of GCKR variants with metabolic phenotypes, including measures of glucose homeostasis, to evaluate the GCKR locus in samples of non-European ancestry and to finemap across the associated genomic interval.RESEARCH DESIGN AND METHODS-We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
249
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(287 citation statements)
references
References 40 publications
34
249
3
1
Order By: Relevance
“…The present study was the first to investigate the associations of rs780092 with risk of incident dyslipidaemia and type 2 diabetes. Our findings are in line with results from previous studies in whites and Asians, in which the GCKR variant reversely associated with TG levels and type 2 diabetes risk [4,6,9,13]. Notably, one prospective cohort study has shown that the T-allele of rs1260326 was strongly associated with lower fasting glucose and, conversely, higher TG during a 9 year study [9].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study was the first to investigate the associations of rs780092 with risk of incident dyslipidaemia and type 2 diabetes. Our findings are in line with results from previous studies in whites and Asians, in which the GCKR variant reversely associated with TG levels and type 2 diabetes risk [4,6,9,13]. Notably, one prospective cohort study has shown that the T-allele of rs1260326 was strongly associated with lower fasting glucose and, conversely, higher TG during a 9 year study [9].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, one prospective cohort study has shown that the T-allele of rs1260326 was strongly associated with lower fasting glucose and, conversely, higher TG during a 9 year study [9]. Another prospective study also demonstrated that the rs1260326 variant was associated with longitudinal changes in TG but not fasting plasma glucose levels [4]. Similarly, a significant association between rs780092 and 5 year change in log 10 TG was also observed in our study, although rs780092 was not significantly associated with increasing levels of fasting plasma glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of GCKR in urate transport is, however, unclear. This protein is known for its role in the control of glucokinase activity and glucose utilization by liver, and other genetic association studies have found the GCKR locus to influence triglyceride levels (79,80).…”
Section: Other Genes Identified By Genetic Association Studiesmentioning
confidence: 99%
“…Even though large consortia meta-analyses have not reported variants near ENPP1, we included it in our analysis because of strong prior associations of rs1044498 with IR. [27][28][29] The C allele at rs1260326 near GCKR is associated with higher IR and lower TG levels 30 ; we therefore used the T alleles at this locus as the risk alleles in analyses of TG levels. Two of the seven SNPs associated with IR are also associated with increased BMI (rs9939609 near FTO and rs11152213 near MCR4).…”
Section: Study Populationmentioning
confidence: 99%